Nurturing Curiosity Beyond Identity Labels to Find the Radical: Notes on What Encouraged Radical Youth to Participate in Transnational Qualitative Research - Benevento, Ayşenur (Springer, 2023)
Researchers interested in expanding our understanding about individuals, who are silenced by majority societies or those who willingly position themselves close to condemned standpoints, need to also think about ways of approaching and encouraging potential research participants. The current paper frames that need as an act of curiosity and an ethical responsibility. With that framing in hand, the paper explains the process of overcoming difficulties related to recruiting radicalized subpopulations of youngsters (154 self-identified Muslim youth with migration backgrounds and 153 native youth who support movements labeled as far right) in a transnational qualitative research conducted in four different countries (Germany, France, Belgium, and the Netherlands) in 2020–2022. Because both groups are subject to the labels imposed on them by the majority societies (e.g., Muslim, Salafi, conservative, fascist, right wing, etc.), the researchers felt the need to be flexible in the ways they address and approach each participant. In the field, the purposeful efforts of recruitment wording for each individual appeared very useful in encouraging this by nature skeptical group of people. The current paper documents the development of this flexible strategy, which I hope will be useful to many qualitative researchers to facilitate their data collection efforts to identify and reach youth that is on the path of radicalization. We would like to encourage academics to stay curious about these two subpopulations of youth and other marginalized, singled out, and stigmatized groups, and consider interviewing as many individuals as possible in order to discover the radicals. © 2023, The Author(s).
Keywords: Curiosity; Identity construction; Participant recruitment; Radicalization; Rapport building